Vaccines - Minhinnick, A; Wilkie, M; McShane, H (Elsevier, 2014)
The Side Effects of Drugs Annuals forms a series of volumes in which the adverse effects of drugs and adverse reactions to them are surveyed. The series supplements the contents of Meyler's Side Effects of Drugs: the International Encyclopedia of Adverse Drug Reactions and Interactions. This review of the January 2012 to June 2013 publications on vaccines covers Bacille Calmette-Guérin vaccine, diphtheria-pertussis vaccines, human papilloma virus vaccine, influenza vaccine, Japanese encephalitis vaccine, measles vaccine, measles-mumps-rubella vaccine, mumps vaccine, rubella vaccine, rotavirus vaccine, smallpox vaccine, varicella vaccine and yellow fever vaccine.